Exploiting Food-Grade Mesoporous Silica to Preserve the Antioxidant Properties of Fresh Olive Mill Wastewaters Phenolic Extracts - Federica Ianni; Andrea Gagliardi; Agnese Taticchi; Maurizio Servili; Nicola Pinna; Aurélie Schoubben; Roccaldo Sardella; Stefano Bruscoli (MDPI AG, 2021)
Fresh olive mill wastewaters phenolic extracts are of great interest as preservatives or fortifying ingredients but are characterized by limited stability. The purpose of this study was to use mesoporous silica to enhance their stability and preserve their antioxidant properties. The phenolic extracts were characterized for their composition by HPLC-DAD and included in a mesoporous matrix with or without a lipid coating. The inclusion complexes were characterized in terms of total phenolic content, radical scavenging capacity and in vitro antioxidative activity and cell compatibility. Besides, inclusion complex stability under different storage conditions (22 and 37 °C, 75% relative humidity, 1 month) was evaluated. The inclusion process was nearly quantitative and modified neither the total phenolic content nor the total antioxidant capacity. None of the inclusion complex concentrations assayed on the HT29 cell line showed toxicity. Moreover, HT29 cells treated with the inclusion complex exhibited a significant antioxidant effect, while the lipid coating impaired the antioxidant activity. The complexes without lipid were stable under all the investigated conditions, while the lipid-coated products were less stable under the more drastic conditions. Overall, inclusion complexes in mesoporous silica have suitable characteristics to be used for different applications, including food supplementation.